ä¸¹æˆŽå¸ƒæ‹‰å›½ç«‹å¤§å¦å¸ˆèŒƒå¦é™¢çš„å¦ç”Ÿ ä½¿ç”¨æ—¶é—´å‰¯è¯â€œæ›¾ç»â€å’Œâ€œå·²ç»â€çš„æŽŒæ¡æƒ…å†µåˆ†æž - Novita, Lyan Dwi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
?? ?????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????2014????????????????????????????????????????????????????????2014???????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????? ???? ?? ?? ???? Abstract Adverbs are an important part of grammar, ?Ceng Jing? and ?Yi Jing? belong to time adverbs.?Ceng Jing? and ?Yi Jing? have shown that the action or the emergence of the state should be earlier than a certain time, and sometimes can be replaced. Therefore, Chinese learners are prone to misunderstandings of the two words, confusion of usage, indiscriminate use, misuse and improper use of the situation. In order to understand the mastery and difficulty of of the students of Mandarin at Tanjungpura University, year of enrollment 2014 against